Soroprevalência de zoonoses em indígenas mato-grossenses - Oliveira, Viviane Karolina Vivi (2023)
Health promotion results from the synergism between knowledge and practices, the role of social determinants on health conditions and the role of governmental and nongovernmental spheres. In its socio-environmental approach, the development of control and prevention policies can prevent the emergence of emerging and re-emerging diseases in indigenous communities, such as Haliti-Paresí, which due to possible immunological susceptibility, close contact with the environment and lifestyle, are in a condition of great vulnerability to be affected by zoonoses. Objective – To verify the seroprevalence of Bartonella henselae, Bartonella quintana, Coxiella burnetii, Leptospira spp. and the related factors of these neglected zoonoses in the Haliti-Paresí indigenous population in 2014 and 2015, highlighting the interface with health promotion in this context. Material and methods – This is a cross-sectional study carried out in 2014 and 2015 in the Haliti-Paresí indigenous populations of the mid-north of Mato Grosso, Brazil. From 73 paired blood serum samples from the Biobank of the Laboratory of Hantaviruses and Rickettsioses of the Oswaldo Cruz Institute, the detection of antibodies of the class IgG anti-Bartonella sp. and anti-Coxiella burnetii IgG by indirect immunofluorescence test for bartonellosis and Q fever, respectively; the microscopic agglutination test was used to diagnose Leptospira sp., the etiologic agent of leptospirosis. Sociodemographic data of the population were collected and entered into EpiInfo 7, and the analysis was performed using absolute and relative frequencies in relation to demographic, socioeconomic and historical characteristics of infections of the diseases under study. The prevalence of antibodies against the researched diseases was estimated and the association between each exposure and outcome was tested for each situation. Results: There was a predominance of female indigenous people (65.75%), aged between 20 and 39 years old (39.73%) and incomplete primary education (42.47%). The prevalent occupational activity was taking care of the home, family, collection in the Cerrado and cultural activities (35.61%). Wooden housing represented 50.68%, followed by traditional indigenous housing (28.77%). There was no seroreactivity for Q fever and leptospirosis in the two years analyzed and no reports of compatible symptoms. Among the aspects that increase the vulnerability to Q fever were the handling of dry straw (50.68%) in 2014 and body contact and/or infestation by ticks (56.16%) in 2015. For leptospirosis, the highlights are if the presence of rodents, seen by46.58% of the indigenous people, and of these, 55.88% claimed to be in the vicinity/inside of the house. For bartonellosis, 5.47% of the samples were seroreactive and during the years investigated, 2.7% of the indigenous people were seroreactive. It was identified that each indigenous family had four to six cats with the function of rodent hunters and that most of these felines had flea infestations. Conclusion - It is believed that other zoonoses are present in this indigenous community and that, due to the difficulty in accessing health services and research, they are not being identified, in addition to the fact that the unspecific symptoms at the beginning of these diseases are confounding factors among other circulating endemic diseases. Thus, health surveillance, through seroepidemiological studies, can point out clinical and epidemiological evidence, providing health services with broader intervention strategies, especially in health education activities, training on differential diagnosis and care references.